Comparation of free radical scavenging activity between seven species of Passiflora L. - Montero, Daniel Antônio Villamil [UNESP]; Bonfim, Filipe Pereira Giardini [UNESP]; Ming, Lin Chau [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; Meletti, L. M. M. (My University, 2014)
Antioxidant capacities of seven species of Passiflora were evaluated through comparation of the free radical DPPH scavenging activity. The studied species included cultivated and traditionally used P. edulis, P. incarnata and P. alata and less common species P. coccinea, P. laurifolia, P. mucronata and P. gardneri. The experimental design was completely randomized with ANOVA and Tukey test as main statistical analyses. The results showed that species of Passiflora had variable antioxidant capacities, ranging from 28 to 95% of free radical DPPH scavenging activity.
Keywords: P. alata; P. coccínea; P. gardneri; P. incarnata; P. edulis; P. laurifólia; P. mucronata; Antioxidant